Silica dust and sarcoidosis in Swedish construction workers. (24th August 2019) - Jonsson, E; Järvholm, B; Andersson, M
Abstract: Background: The aetiology of sarcoidosis is not well established. In previous studies, smoking has been negatively associated with sarcoidosis and there are some indications of an association between exposure to silica dust and sarcoidosis. Aims: To study the risk of sarcoidosis in relation to silica dust exposure. Methods: A longitudinal cohort of construction workers linked with a registry of Swedish inpatient diagnoses. Workers were designated as exposed or unexposed to silica based on job titles in a job–exposure matrix. The relative risk (RR) was analysed with Poisson regression adjusting for age and smoking. Results: We identified 371 cases of sarcoidosis among 297 917 male workers. There was an increased risk of sarcoidosis in the medium- to high-exposure group [RR 1.83 (95% confidence interval CI 1.14–2.95)]. A stratified analysis according to smoking showed that ever-smoking workers had an increased risk of sarcoidosis if highly exposed to silica dust [RR 2.44 (95% CI 1.37–4.33)] compared to non-exposed ever-smokers. The risk of non-smokers highly exposed to silica was not significantly increased [RR 1.07 (95% CI 0.72–1.58)] compared to non-exposed non-smokers. Conclusion: The study indicates an increased risk of developing sarcoidosis in ever-smoking men exposed to silica.